Field Oriented Economic Model Predictive Control for Permanent Magnet Synchronous Motors⁎This research was supported by the German Federal Ministry for Economic Affairs and Energy (BMWi) via eco4wind (0324125B) and DyConPV (0324166B), and by DFG via Research Unit FOR 2401. Issue 2 (2020) - Geweth, D.; Zanelli, A.; Frison, G.; Vollmer, U.; Diehl, M.
Abstract: This paper proposes a novel nonlinear model predictive control approach for permanent magnet synchronous machines (PMSM). The optimization problem is formulated as a field oriented economic model predictive control (FO-EMPC) problem and therefore a target selector is not necessary. A dq-model of the PMSM with spherical voltage and current constraints is taken into account. A terminal set and a terminal penalty are introduced to mitigate stability and convergence issues with a short prediction horizon. The performance of the proposed control scheme is demonstrated in a simulation study on a personal computer and in a hardware-in-the-loop simulation, which show that the transition time is reduced by more than one order of magnitude with respect to state-of-the-art approaches, especially when the voltage constraint becomes active.